فاعلية استراتيجية الرحلات المعرفية عبر الويب Web Quest في تدريس التاريخ لتنمية المهارات الحياتية والفهم التاريخي لدى تلاميذ الصف الثاني الإعدادي - زيدان، إيمان خالد محمود; خميس، خميس محمد (جامعة مدينة السادات - كلية التربية, 2023)
هدف هذا البحث إلى التعرف على أثر استخدام استراتيجية الرحلات المعرفية عبر الويب في تدريس التاريخ على تنمية مهارات الفهم التاريخي والمهارات الحياتية لدى تلاميذ الصف الثاني الإعدادي، تم استخدام المنهج التجريبي المعتمد على تصميم مجموعتين المجموعة التجريبية والمجموعة الضابطة، مع التطبيق القبلي والبعدي لأدوات البحث المتمثلة في: (اختبار مهارات الفهم التاريخي والمهارات الحياتية)، لاختبار صدق الفرضيات والإجابة عن أسئلة البحث. تكونت مجموعة البحث من (٦٠) تلميذا من تلاميذ الصف الثاني الإعدادي بمدرسة عبد المنعم عسل اللغات بسما دون بإدارة أشمون التعليمة بمحافظة المنوفية. وقد كشفت نتائج البحث عن وجود فرق دال إحصائيا عند مستوى (0.05) بين متوسطي دراجات تلاميذ المجموعة التجريبية ودراجات تلاميذ المجموعة الضابطة في التطبيق البعدي لاختبار مهارات الفهم التاريخي والمهارات الحياتية ككل ولكل مهارة على حدة لصالح المجموعة التجريبية، ووجود فرق دال إحصائيا عند مستوى (0.05) بين متوسطي دراجات تلاميذ المجموعة التجريبية في التطبيقين القبلي والبعدي لاختبار مهارات الفهم التاريخي والمهارات الحياتية ككل، ولكل مهارة على حدة لصالح التطبيق البعدي؛ مما يدل على تأثير استراتيجية الرحلات المعرفية عبر الويب في تدريس التاريخ على تنمية مهارات الفهم التاريخي والمهارات الحياتية لدى تلاميذ الصف الثاني الإعدادي، لذا فقد أوصى البحث بضرورة الاهتمام باستخدام الرحلات المعرفية عبر الويب في تدريس الدراسات الاجتماعية بصفة عامة، وتدريس التاريخ بصفة خاصة. The aim of this research is to identify the effect of using the strategy of cognitive trips via the web in teaching history on the development of historical understanding and life skills among secondary school students then using, the experiments approach was used on the design of two groups, the experiment group and the control group, with the pre and post application of the research tool represented in (Historical comprehension and life skills test) to test the validity of the hypotheses and answer the research questions the research group consisted of (60) students from the second year of middle school at Abdel Moneim Asal Language school on samadon, managed by Ashmoun Education, The result of the research revealed that there is a statistically significant difference at level 0.05 between the mean scores of the students of the experimental group and the scores of the control group students in the post application to choose historical comprehension skills and life skills as a whole and for each skill separately in favor of the experimental group, and the scores of the control group students in the post application to choose historical comprehension skills and life skills as a whole and for each skill separately in favor of the experiments group, and there is a statistically significant a difference between the among scores of the experimental group students in the pre and post, Applications test the skills of historical understanding and life skills as a whole, and for each skills separately the benefit of the post application, this indicates the effect of the strategy of cognitive trips through the web in the history lesson on the development of historical comprehension skills and life skills among second grade middle school students, Therefore the research lost need pay attention to the use of cognitive homeys through the web in social studies in general, and the teaching of history in particular.
Keywords: الاستراتيجيات التعليمية -- مادة التاريخ -- مهارات الفهم التاريخي -- طلبة المرحلة الإعدادية